Determination of Appropriate Method to Measure Mean Texture Depth (MTD) for Bicycle Lane Surface - M.S. Nemmang; N.M. Khaidir; S.T.M.S.T. Arif; J.S. Ho; A. Shabadin (Journal of the Society of Automotive Engineers Malaysia, 2022)
A bicycle is described as a two-wheel vehicle, propelled by pedals and steered by handlebars attached to the front wheel. In Malaysia, it is difficult to obtain the exact number of bicycles on the road because they are not registered with the authority. However, based on observation, it has seen a tremendous increase in the number of bicycle activities on the road. The increment was anticipated due to the government initiatives on green environment and reducing carbon monoxide from transportation. In supporting the initiatives, the government has also taken a proactive measure to provide more bicycle facilities on the road. In general, an optimal design of a bicycle facility must be capable of providing safety, comfort to road users, and high accessibility to the road network. Because of the lack of bicycle facility design standard available in Malaysia, various bicycle design was observed. Bicycle lane pavement is one of the dissimilarities observed. Since the quality of pavement surface is vital in ensuring safety, this study is aimed to investigate the skid resistance ability provided by a different type of bicycle lane pavement. Besides measuring the Skid Resistance Value (SRV), skid resistance can also be investigated by measuring the pavement Mean Texture Depth (MTD). This study utilized the Out Flow Meter Test and Sand Patch Test to measure the MTD value. Data collection was conducted at 20 locations including on-road and off- road bicycle lanes. It was found that there is a good correlation between the outflow meter test and the sand patch test for bicycle lane pavement.